Analisis Kebutuhan Taruna terhadap Pengembangan Bahan Ajar Digital Pada Mata Kuliah Familiarisasi Pesawat Berbasis Platform Learning Management System Politeknik Penerbangan Palembang - Sutiyo Sutiyo; M. Permadi Yosa Nugraha; Alfian Meidy Anes; Sabrina Ramdhani (Politeknik Penerbangan Makassar, 2022)
This study aims to analyze the needs of cadets for the development of digital teaching materials in the aircraft familirization course based on the Moodle LMS platform at Poltekbang Palembang. The design of the development model in this study used the ADDIE step (Analysis, Design, Develop, Implementation, Evaluation). However, this article only discusses part of the analysis stage, namely regarding the needs of cadets for the development of digital teaching materials in the aircraft familirization course based on the Moodle LMS platform at Poltekbang Palembang. The research subjects in this study were 45 Poltekbang Palembang cadets who took the aircraft famiilrization course. Data collection techniques used include non-test techniques. The instrument used is a needs questionnaire whose development refers to a modified Likert Scale with 4 answer choices, namely strongly agree, agree, disagree, and strongly disagree. Data analysis techniques in this study used qualitative techniques and quantitative techniques. The results of the study indicate that cadets need digital teaching materials based on the Moodle LMS platform in the aircraft familirization course.